Предмет: Алгебра, автор: nikita210400

Y''+2y'=-2e^x(sinx+cosx)

Ответы

Автор ответа: NNNLLL54
4

y''+2y'=-2e^{x}(sinx+cosx)\\\\1)\; \; y''+2y'=0\; \; ,\; \; k^2+2k=0\; \; ,\; \; k(k+2)=0\; \; ,\; \; k_1=0\; ,\; k_2=-2\\\\y_{obsh.odn.}=Y=C_1+C_2e^{-2x}\\\\2)\; \; f(x)=-2e^{x}(sinx+cosx)\; \; ,\; \; 1+i\ne 0\; ,\; \; 1+i\ne -2\; \; \to \\\\y_{chastn.}=\tilde{y}=e^{x}\cdot (Acosx+Bsinx)\\\\\tilde{y}'=e^{x}\cdot (Acosx+Bsinx)+e^{x}\cdot (-Asinx+Bcosx)\\\\\tilde {y}''=e^{x}\cdot (Acosx+Bsinx)+e^{x}\cdot (-Asinx+Bcosx)+e^{x}\cdot (-Asinx+Bcosx)+\\\\+e^{x}\cdot (-Acosx-Bsinx)

\tilde {y}''+2\tilde {y}'=4e^{x}\cdot (-Asinx+Bcosx)+2e^{x}\cdot (Acosx+Bsinx)\\\\4e^{x}\cdot (-Asinx+Bcosx)+2e^{x}\cdot (Acosx+Bsinx)=-2e^{x}\cdot (sinx+cosx)\\\\(-4A+2B)\cdot sinx+(4B+2A)\cdot cosx=-2sinx-2cosx\\\\\left\{\begin{array}{cc}-4A+2B=-2\\2A+4B=-2\end{array}\right\; \; \left\{\begin{array}{cc}-2A+B=-1\\A+2B=-1\end{array}\right\; \; \left\{\begin{array}{cc}A=\frac{1}{5}\\B=-\frac{3}{5}\end{array}\right\\\\\\3)\; \; y_{obsh.neodn.}=Y+\tilde {y}=C_1+C_2e^{-2x}+e^{x}\cdot (\frac{1}{5}\, cosx-\frac{3}{5}\, sinx)


nikita210400: А почему там 4?
NNNLLL54: потому что запишите выражение y''+2y' и подсчитайте
Похожие вопросы